THE RECORD OF USING PICTURE SERIES TO DEVELOP STUDENTS’ WRITING SKILLS - Wahono, Suparwoto Sapto; Afifah, Kholidatul (University of Kuningan, 2022)
Based on the observations results, the learners had difficulty in exploring their ideas. They took more time and could only write some sentences. Another barrying that students faced was that they could not write well-organized paragraphs. The students also often had difficulty in learning grammar, especially English tenses. Lack of vocabulary mastery was also the cause of writing difficulties. They stated that writing in English was difficult and complicated. That’s why the researchers used classroom action research to apply picture serias as media. It was conducted by two cycles.The subjects were seventeen students of tenth grade science student at Banyuwangi. To get the data, the researchers used observation, interview, and test. The research result could be stated that using the picture series improved the learners’ writing narrative text competence. They could improve their writing gradually from the first cycle to the second one. The picture series that implemented significantly improved their skill in English writing.